Severity of tricuspid regurgitation predicts risk of recurrence of atrial fibrillation after pulmonary vein isolation - Jan Wintrich; Dimitrios Bismpos; Anika Teusch; Valerie Pavlicek; Patrick Fischer; Felix Mahfoud; Michael Böhm; Christian Ukena (ESC Heart Failure)
Abstract Aims Tricuspid regurgitation (TR) results in right atrial remodelling, thus promoting the formation of a substrate for atrial fibrillation (AF). In turn, AF may cause TR by annulus dilatation. We investigated whether the presence of TR affects the efficacy of pulmonary vein isolation (PVI) for AF. Methods and results In patients undergoing PVI, we compared the severity of TR before and 6 months after the procedure. Moderate to severe TR was defined as advanced. Moreover, we investigated whether the severity of TR, at baseline and 6 months after PVI, predicted the recurrence of AF. Out of 320 patients, advanced TR at baseline was documented in 13.1%. Six months after PVI, the proportion of patients with advanced TR (13.1% to 7.2%; P < 0.001) decreased significantly. Compared with patients with post‐interventional improvement of advanced TR, right atrial (RA) dilatation at baseline was more pronounced in patients without TR improvement (RA area 20.2 ± 4.4 vs. 26.6 ± 8.3 cm). The presence of advanced TR, particularly without improvement during the follow‐up, increased the risk of AF recurrences compared with patients without advanced TR. Even after propensity‐score matching, TR at baseline remained an independent risk predictor regarding recurrent AF [hazard ratio 2.2 (95% confidence interval, 1.1–4.9); P = 0.045]. Advanced MR was not associated with increased risk of AF. Conclusions In AF patients undergoing PVI, the presence of advanced TR, particularly without improvement 6 months after the procedure, was associated with an increased risk of AF recurrences.